2017
DOI: 10.1101/157636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic risk for schizophrenia influences substance use in emerging adulthood: An event-level polygenic prediction model

Abstract: Background: Emerging adulthood is a peak period of risk for alcohol and illicit drug use. Recent advances in psychiatric genetics suggest that the co-occurrence of substance use and psychopathology arises, in part, from a shared genetic etiology. We sought to extend this research by investigating the influence of genetic risk for schizophrenia on trajectories of four substance use behaviors as they occurred across emerging adulthood.Method: Young adult participants of non-Hispanic European descent provided DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A joint analysis may uncover genetic mechanisms that cannot be discovered in a single analysis (Mukherjee et al, 2013). For example, recent studies have revealed overlapping genetic factors that influence multiple psychiatric disorders (Pain et al, 2018), genetic correlations between schizophrenia, ADHD, depression, and cannabis use (Walters et al, 2018), as well as an association between schizophrenia and illicit drug use (Mallard et al, 2018). Also, co-occurrences of substance use disorders (SUDs) and psychopathology have been observed in national epidemiologic Figure 1: Illustration of the existing challenges when conducting a joint analysis on two independently collected data sets with two different phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…A joint analysis may uncover genetic mechanisms that cannot be discovered in a single analysis (Mukherjee et al, 2013). For example, recent studies have revealed overlapping genetic factors that influence multiple psychiatric disorders (Pain et al, 2018), genetic correlations between schizophrenia, ADHD, depression, and cannabis use (Walters et al, 2018), as well as an association between schizophrenia and illicit drug use (Mallard et al, 2018). Also, co-occurrences of substance use disorders (SUDs) and psychopathology have been observed in national epidemiologic Figure 1: Illustration of the existing challenges when conducting a joint analysis on two independently collected data sets with two different phenotypes.…”
Section: Introductionmentioning
confidence: 99%